GC-MS Characterization and Bioactivity Study of Eucalyptus globulus Labill. (Myrtaceae) Essential Oils and Their Fractions: Antibacterial and Antioxidant Properties and Molecular Docking Modeling - Abdessamad Ait benlabchir; Kawtar Fikri-Benbrahim; Amina Moutawalli; Mohammed M. Alanazi; Asma Halmoune; Fatima Zahra Benkhouili; Asmaa Oubihi; Atul Kabra; Elbatoul Hanoune; Hamza Assila; Zineb Benziane Ouaritini (MDPI AG, 2024)
Background/Objectives: Eucalyptus globulus is a medicinal plant extensively used by the Moroccan population for treating a range of illnesses, especially respiratory conditions. Methods: This study aimed to assess the antioxidant and antibacterial properties of E. globulus essential oil and its individual fractions (F1, F2, and F3). Antioxidant activity was evaluated through iron-reducing power, 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays. Antibacterial activity was tested using disk diffusion and dilution methods, supported by molecular docking studies. Furthermore, GC-MS analysis was conducted on the essential oil and its individual fractions. Results: GC-MS analysis identified the major compounds in the essential oil and its fractions as eucalyptol (62.32-42.60%), globulol (5.9-26.24%), o-cymene (6.89-24.35%), cryptone (7.10-15.95%), terpinen-4-ol (2.43-15.24%), and α-pinene (2.46-7.89%). Fraction F3 displayed the highest antioxidant activity in DPPH (IC50 = 3.329 ± 0.054 mg/mL) and ABTS assays (IC50 = 3.721 ± 0.027 mg/mL), while fraction F2 was most effective in the FRAP assay (IC50 = 1.054 ± 0.008 mg/mL). The essential oil and its fractions also showed antibacterial activity against Staphylococcus aureus, Staphylococcus epidermidis, Klebsiella pneumoniae, Enterobacter cloacae, Escherichia coli, and Acinetobacter baumannii. Molecular docking further corroborated these findings, supporting both antioxidant and antibacterial activities. Conclusions: The present findings demonstrate the antioxidant and antimicrobial properties of Eucalyptus globulus essential oil and its fractions, underscoring the need for further research to confirm their medicinal potential and explore pharmaceutical applications.